2022
DOI: 10.1136/bmjopen-2022-062122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HEAT therapy in patiEnts with type 2 Diabetes mellitus (HEATED): protocol for a randomised controlled trial

Abstract: IntroductionThe burden of type 2 diabetes mellitus (T2DM) is increasing worldwide. Heat therapy has been found effective in improving glycaemic control. However, to date, there is a lack of randomised controlled studies investigating the efficacy of heat therapy in T2DM. Therefore, we aim to investigate whether heat therapy with natural thermal mineral water can improve glycaemic control in patients with T2DM.Methods and analysisThe HEAT therapy in patiEnts with type 2 Diabetes mellitus (HEATED) Study is a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Thus, proposing NO pathway as one molecular mechanism via which heat exposure may influence the responses of keratinocytes in high glucose condition. As recently proposed in clinical studies, the duration of heat exposure is a key when investigating its therapeutic effect on diabetes [16][17][18][19]. Given this and our results indicating the altered NO production upon acute heat exposure, we aimed to explore how longer heat exposure, referred as to the chronic exposure, may influence its levels.…”
Section: Heat Exposure Alters the Metabolic Profile Of Skin Keratinoc...mentioning
confidence: 90%
See 2 more Smart Citations
“…Thus, proposing NO pathway as one molecular mechanism via which heat exposure may influence the responses of keratinocytes in high glucose condition. As recently proposed in clinical studies, the duration of heat exposure is a key when investigating its therapeutic effect on diabetes [16][17][18][19]. Given this and our results indicating the altered NO production upon acute heat exposure, we aimed to explore how longer heat exposure, referred as to the chronic exposure, may influence its levels.…”
Section: Heat Exposure Alters the Metabolic Profile Of Skin Keratinoc...mentioning
confidence: 90%
“…Recently, clinical studies reported that heat therapy has beneficial results in improving insulin sensitivity and glycemic control for diabetic patients [18,19,52,53]. Based on this, we aimed to explore whether frequent heat exposure may improve the levels of NO and consequently HSP-70 protein in high glucose-maintained keratinocytes.…”
Section: Repetitive Heat Exposure Improves the Levels Of No And Hsp-7...mentioning
confidence: 99%
See 1 more Smart Citation